Pengaruh Green Accounting Terhadap Sustainability Ekonomi Pada Industri Perkebunan Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Beata Sakristi Sarni; Vunky Syahrial; Maria Yovita R Pandin (Jurnal Riset Ekonomi dan Akuntansi, 2023)
The purpose of this research is to study and analyze the impact of green accounting on the sustainability of companies in plantations listed on the Indonesian Stock Exchange. This research is a quantitative research obtained by taking secondary data and determining the sample by purposive sampling using the Slovin formula. In this study, the number of samples was 18 manufacturing companies and the analysis technique used in this study was simple linear analysis. In this study, green accounting is assessed using company annual report data and environmental protection level data (PROPERA) obtained from the Ministry of Environment and Forestry. Based on survey results, green accounting has a positive impact on the financial sustainability of companies in the plantation sector and includes environmental costs in the company's annual report.